KOMUNIKASI RITUAL PAWAI OGOH-OGOH SEBAGAI IMPLEMENTASI DALAM TRI HITA KARANA - Ni Luh Eka Yuli Anggreni (Widya Sandhi Jurnal Kajian Agama Sosial dan Budaya, 2023)
The Ogoh-ogoh parade is one of a series of Nyepi activities. In the implementation of the ogoh-ogoh parade which was held in the city of Mataram, it did not only involve Hindus, but also Muslims, Buddhists, and Christians. Ogoh-Ogoh is one of the works of sculpture that depicts the embodiment of Bhuta kala, Bhuta kala in Hinduism is described as the embodiment of a giant whose figure is known for its large and frightening size. The purpose of this study is to describe and analyze the implementation and values ​​contained in the teachings of tri hitakarana in the tradition of the ogoh-ogoh parade in Mataram City. This study used qualitative research methods. The results of this study are as follows: Ritual Communication of the Ogoh-Ogoh Parade as Implementation in Tri Hitakarana, including, 1) The Parhyangan conception is implemented before carrying out the ogoh-ogoh parade, where before the event begins the community performs a melaspas ceremony. 2) Conception Pawongan is the concept of harmonization between fellow humans, the implementation of which in the parade is not only the Hindu community who are involved as paratroopers or gamelan musicians, but there are also non-Hindu relatives that we meet bringing kecimol, gendang beleq and even barong sai to participate in the celebration and celebration. the success of the ogoh-ogoh parade. 3) The concept of Palemahan is implemented when after carrying out the ogoh-ogoh parade, the community then performs a mass mecaru ceremony or at their respective homes. The values ​​contained in the Ritual Communication of the Ogoh-Ogoh Parade as Implementation in the Tri Hitakarana are, 1) Religious or Spiritual Values, believing in the existence of God which is believed by Hindus or the people of Mataram City. 2) Social Values ​​and Religious Tolerance, mutual respect among Hindus or among each other despite different religions and beliefs, without anyone looking at social status, whether position, caste or wealth in order to achieve common goals, all work hand in hand enthusiastically, sincerely, sincerely and concern for others. 3) Art value, contained in the manufacturing process, where in making ogoh-ogoh techniques are needed in making and have a high artistic spirit by having an artistic soul so that person can pour ideas according to the desired imagination, not only looks good to the eye but also able to give an impression and meaning to everyone who observes the work of art.